Therapeutic evaluation and analysis of complications of ethanol sclerotherapy for intramuscular vascular malformations: a single-center retrospective study - Jin, Cai-Jun; Wang, Qian; Wang, Min; Chen, Yong; Yuan, Si-Ming (Frontiers in Surgery, 2023)
Background: Intramuscular venous malformations (IMVM) can cause pain and contracture deformity, leading to dysfunction of limbs. Ethanol sclerotherapy is one of the main treatments for IMVM. This article aims to evaluate the efficacy and the complications of intravascular ethanol sclerotherapy of IMVM, and summarize experiences for clinical reference.We retrospective analyzed data of 118 IMVM patients treated with ethanol sclerotherapy in our center from 2006 to 2021. The clinical data were recorded by plastic surgeons using standardized collection proforma. And patients were followed up for timefrom6 months to 5 years to assess the relief of symptoms, the change of lesion size and the recovery of functional outcomes, and analyze long-term complications.The clinical symptoms of the patients in this group included pain, swelling and limited movement. On average, 5.61 mL (range 2-14mL) ethanol was used in the process of sclerotherapy per time. Intraoperative complications and the early postoperative complications were all relieved at the end of follow-up after timely treated.According to MRI, the lesions of 19% cases were significantly decreased, 39% were slightly decreased. During the follow-up period, only 8 of 118 patients had long-term complications related to sclerotherapy.Although ethanol sclerotherapy is an effective first-line treatment for IMVM, there are a variety of adverse reactions, short-term and long-term complications.Surgeons need to perform operations prudently and give timely treatment to 3 postoperative complications.